WAREHOUSE RECEIPTS FUNCTIONING TO REDUCE MARKET RISK - Jovičić, Daliborka; Jeremić, Ljiljana; Milićević, Lazar; Zeremski, Aleksandar (Economics of Agriculture, 2014)
Cereal production underlies the market risk to a great extent due to its elastic demand. Prices of grain have cyclic movements and significant decline in the harvest periods as a result of insufficient supply and high demand. The very specificity of agricultural production leads to the fact that agricultures are forced to sell their products at unfavorable conditions in order to resume production. The Public Warehouses System allows the agricultures, who were previously unable to use the bank loans to finance the continuation of their production, to efficiently acquire the necessary funds, by the support of the warehouse receipts which serve as collaterals. Based on the results obtained by applying statistical methods (variance and standard deviation), as a measure of market risk under the assumption that warehouse receipts prices will approximately follow the overall consumer price index, it can be concluded that the warehouse receipts trade will have a significant impact on risk reduction in cereal production. Positive effects can be manifested through the stabilization of prices, reduction of cyclic movements in the production of basic grains and, in the final stage, on the countrys food security.